Pengaruh Kepuasan Kerja Dan Lingkungan Kerja Terhadap Motivasi Kerja CV Artha Mandiri Group Kabupaten Merangin - Windi Indra Maldini (Science of Management and Students Research Journal (SMS), 2022)
CV Artha Mandiri Group is a company (persero) engaged in equiqment rental and contractor. This study aims to describe job satisfaction, work environment, and work motivation of CV Artha Mandiri Group Merangin Regency, to determine and analyze the effect of job satisfaction and work environment simultaneously and partially. To answer the research objectives, the author uses theoretical studies related to research variables, namely job satisfaction, work environment, and work motivation. In addition, the author also looks for relevant previous research in the form of articles/journals and previous theses to support this research. This research uses quantitative methods. With the population in this study were employees of CV Artha Mandiri Group, Merangin Regency, totaling 98 employees. The results of multiple linear regression analysis obtained the equation persamaan . Meanwhile, from the hypothesis testing carried out, the results show that job satisfaction and work environment have a significant effect on work motivation simultaneously, while partially the work environment has no significant effect on work motivation. Based on the results of data analysis and discussion in this study, it can be concluded that CV Artha Mandiri Group Merangin Regency has high job satisfaction, poor work environment, good motivation. In addition, job satisfaction simultaneously and partially has a positive and significant effect on work motivation, work environment partially has no positive and significant effect on work motivation at CV Artha Mandiri Group, Merangin Regency. For this reason, it is hoped that in the future it can focus more on improving a more conducive work environment so that employee motivation is higher than before.